Lightweight Edge-Based Security System Design for DDoS Attack Mitigation in Industrial IoT Infrastructure - Amrullah, Ata (Intellithings Journal, 2024)
The rapid integration of the Industrial Internet of Things (IIoT) into industrial control systems (ICS) has greatly improved automation and operational efficiency, but it has also introduced new cybersecurity risks for critical infrastructure. Distributed Denial of Service (DDoS) attacks, in particular, pose a significant threat by potentially disrupting real-time operations, compromising safety, and causing physical damage. Traditional centralized methods for mitigating DDoS attacks often do not meet the low-latency, high-reliability, and resource-constrained requirements of IIoT environments. To address these challenges, this paper proposes a lightweight, edge-based security system specifically designed for real-time DDoS mitigation in IIoT infrastructures. The proposed architecture leverages the local processing capabilities of edge gateways, integrates efficient machine learning models for anomaly detection, and implements rapid response mechanisms. By focusing on resource efficiency and effective threat neutralization close to the source, the system aims to safeguard the integrity and availability of critical industrial processes. This paper outlines the system’s main components, highlights its lightweight design, and discusses ongoing challenges, providing a foundational framework for enhancing IIoT security against the growing landscape of cyber threats.